2015
DOI: 10.1109/tie.2015.2420672
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal PSpice Modeling and Simulation of Power Modules

Abstract: Integrated Power Electronics Modules (IPEMs) represent an innovative typology of power electronics assemblies able to guarantee several advantages such as increasing of power density, better management of the thermal flows and a significant reduction of the package sizes. Their characteristics make them suitable for applications like motor drives or power conditioning. IPEMs usage in emerging fields like hybrid automotive traction and electric generation from renewable energy sources is continuously increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…It can be observed that, with increasing temperature, the thermal conductivity and density of the PE decreases while the specific heat capacity increases until 125 • C (i.e., the melting point of PE), and above this temperature, it becomes nearly constant. This shows that the thermal resistance and thermal capacitance of PE increases with an increase in the temperature from room temperature to 125 • C and then becomes nearly constant afterwards, according to Equations (6) and (7), respectively. Figure 11b shows the peak temperatures of the third comparison.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…It can be observed that, with increasing temperature, the thermal conductivity and density of the PE decreases while the specific heat capacity increases until 125 • C (i.e., the melting point of PE), and above this temperature, it becomes nearly constant. This shows that the thermal resistance and thermal capacitance of PE increases with an increase in the temperature from room temperature to 125 • C and then becomes nearly constant afterwards, according to Equations (6) and (7), respectively. Figure 11b shows the peak temperatures of the third comparison.…”
Section: Resultsmentioning
confidence: 79%
“…By splitting the layer geometry into three tubes, the thermal resistance for the inner layers Li200-Li2000 and the outer layers Lo200-Lo800 was calculated using Equation (6), and the thermal capacitance was calculated using Equations (7) and (9). The thermal resistance of the remaining outer three layers, Lo1000-Lo2000, was calculated using Equations (5) and (4), and the thermal capacitance was calculated using Equations (8) and (7). The material properties used for the HDPE layer calculations were ρ = 950 kg/m 3 , λ = 0.51 W/ • C·m, and c ρ = 2000 J/kg· • C, and for the LDPE layer, they were were ρ = 900 kg/m 3 , λ = 0.36 W/ • C·m, and c ρ = 2300 J/kg· • C. parameters for each of these three tubes in the first layer can be computed by considering the onedimensional heat flow in the radial direction [23].…”
Section: Computed Rc Thermal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling and thermal performance analysis of heatsinks using simulation platforms have been reported in several literatures [28][29][30][31][32]. Many simulation software are available commercially such as: COMSOL Multiphysics, FLUENT, ANSYS, Pro-MECHANICA, etc.…”
Section: Model Outlinementioning
confidence: 99%
“…Many simulation software are available commercially such as: COMSOL Multiphysics, FLUENT, ANSYS, Pro-MECHANICA, etc. that use numerical methods, Finite Element and Finite Volume Methods (FEM and FEV) along with Computer Aided Design (CAD) tools to model the thermal performance of heatsinks [28][29][30][31][32].…”
Section: Model Outlinementioning
confidence: 99%